(untitled) (Journal of Parents and Teachers, 2014)
The following article discusses some aspects of the new science fiction saga written by J.K. Rowling, Harry Potter. It is described as a parable about the world, human beings and education. In these books the characters are characterised by being wizards and attending Hogwarts, a school of magic and wizardry, and during their first year they will be assigned to a house (Gryffindor, Hufflepuff, Ravenclaw or Slytherin) according to their qualities. This saga also touches on other themes such as daily life, family, friendship, love, education, etc. But the article looks at an enviable character (Albus Dumbledore) and the school, as well as whether fantasy has a place in our classrooms.